Antimicrobial Nanoformulations Based on Schinus areira Essential Oil - Cutró, Andrea Carmen (2023)
The goal of this research was to create an antibacterial formulation from Scinus areiraessential oil (EO) that could spread in water. To achieve this, we developed liposomal formulationsof DMPC (1,2-dimyristoyl-sn-glycero-3-phosphocholine) or DPPC (1,2-dipalmitoyl-sn-glycero-3-phosphocholine) that encapsulated the EO. In addition, we utilized the EO as a reducing andstabilizing agent to synthesize silver nanoparticles (AgNPs). The nanoformulations were characterizedby determining their size and zeta potential. In the case of liposomal formulations, chemicalcomposition, and encapsulation efficiency were also determined. Furthermore, antimicrobial activitystudies against Gram-positive and Gram-negative model bacteria were carried out for both kindsof formulations. The results obtained showed the successful encapsulation of the S. areira EO inmultilamellar liposomes of phosphatidylcholine with high efficiency. DPPC liposomes have proven tobe a better encapsulation system, retaining more monoterpenes from the EO and therefore presentingantimicrobial activity against S. aureus with an minimal inhibitory concentration (MIC) value of3 mg/mL of EO. On the other hand, it was also possible to obtain AgNPs by using S. areira EO,which showed antimicrobial activity against S. aureus and E. coli at low concentrations of EO, withMIC values of 6.68 g/mL and 3.4 g/mL of silver, respectively. The data obtained will contributeto enhancing the biotechnological value of natural products derived from native plant species inArgentina. This will be achieved through the generation of novel formulations with antibacterialactivity and potential bioavailability.